Nuclear morphometry and texture analysis of B-cell non-Hodgkin lymphoma: Utility in subclassification on cytosmears - Gupta, Shilpa; Gupta, Ruchika; Singh, Sompal; Gupta, Kusum; Kudesia, Madhur (Diagnostic cytopathology, 2010)
Non‐Hodgkin lymphoma (NHL) is a heterogeneous group of lymphoid neoplasms and accurate subclassification is an essential prerequisite for proper management of patients. This study was aimed at evaluating the utility of nuclear morphometry and textural features on cytology smears to classify the cases of NHL on aspiration cytology. Fine needle aspiration smears of 50 cases of B‐cell NHL were included. Various morphometric and texture parameters were obtained by manually tracing the nuclei on digitized images in each case and discriminant analysis performed using various features taken individually as well as all together. The percentage of cells correctly classified to a particular NHL subtype using the discriminant functions so obtained was noted. Our results show that discriminant analysis done on size parameters could correctly classify a greater number of cells than on shape parameters (36.4% vs. 21.2%, respectively). Texture parameters based on single pixel values (first order texture) were inferior (42.8%) to those based on pair of pixels (58.7%) in subtyping of cells. Discriminant analysis based on color parameters was more effective (61.9%) as compared to rest of the morphometric and textural parameters. Using all the morphometric and textural parameters together, 83.3% of cells could be correctly classified to a particular NHL subtype. The present study, perhaps the first study of detailed morphometric analysis on cytosmears, shows that satisfactory classification of NHL on aspiration cytology is possible using nuclear morphometry and textural parameters considered together. These results are promising for further studies on this subject and development of automated cytodiagnosis. Diagn. Cytopathol. 2010. © 2009 Wiley‐Liss, Inc.